Peranan Tuntutan Kerja dan Sumber Daya Kerja terhadap Keterikatan Kerja Wanita Karir - Annisaa Miranty Nurendra (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2016)
The purpose of this study is to explore the role of job demands, job resources and work engagement among dual career women. The hypotheses to be tested was : 1 ) there is correlation between job demands and work engagement among dual career women, 2) there is correlation between job resources and work engagement among dual career women, 3) there is moderating effect from job resources at the correlation between job demand and work engagement among dual career women. This tudy engaged 62 woman employee, which have characteristics as married and have been working for minimum 1 years. Job demands and job resources scales are applied at this study, together with the adaptation of Utrecth Work Engagement Scale (UWES). The analysis showed that :1) job demands is not correlated with work engagement, 2) job resources is correlated with work engagement. Keywords : job demands, job resources, work engagement, dual career women